2019
DOI: 10.1002/asia.201900496
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Reactivity of Molybdenum–Trihalide Complexes Bearing PCP‐Type Pincer Ligands

Abstract: Molybdenum–iodide complexes bearing a PCP[1] ligand have been found to work as excellent catalysts toward ammonia formation under ambient reaction conditions among dinitrogen‐bridged dimolybdenum complexes and other molybdenum complexes bearing PNP and PCP[2] ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…of NH 3 production per catalyst, which was 35 times higher activity than the N 2 -bridged Mo 2 complex. Furthermore, they examined the effect of PCP-type carbene ligands of 1,3-bis((di-tert-butylphosphino)methyl)benzimidazol-2-ylidene (PCP-1), 1,3-bis(2-(di-tertbutylphosphino)ethyl)imidazol-2-ylidene (PCP-2) [126] (Scheme 16). The PCP-1-Mo (33) produced 100 equiv.…”
Section: Synthetic Electrocatalysts For N2 Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…of NH 3 production per catalyst, which was 35 times higher activity than the N 2 -bridged Mo 2 complex. Furthermore, they examined the effect of PCP-type carbene ligands of 1,3-bis((di-tert-butylphosphino)methyl)benzimidazol-2-ylidene (PCP-1), 1,3-bis(2-(di-tertbutylphosphino)ethyl)imidazol-2-ylidene (PCP-2) [126] (Scheme 16). The PCP-1-Mo (33) produced 100 equiv.…”
Section: Synthetic Electrocatalysts For N2 Reductionmentioning
confidence: 99%
“…Interestingly, the mutation by β-98 His improved electron-accepting ability from an un-natural reducing agent to promote reductions of azide (N 3 − ) or nitrite (NO 2 − ) to NH 3 [147]. Using electron mediators such as polyaminocarboxylate-ligated Eu [126] and polyallylamine (PAA) polymer-CoCp 2 [148] further improved reduction efficiencies. Rather in the presence of Fe-protein, without using an additional electron mediator, electron transfer between Fe-protein and FeMocluster became slow.…”
Section: Nitrogenase-electrode Biohybridmentioning
confidence: 99%
“…[8] Their Mo- fixation. At present, a molybdenum trihalide complex is known as the most effective metal complex that catalyzes nitrogen fixation under ambient conditions, [9] while titanium-, [10] vanadium-, [11] iron-, [12][13][14][15][16][17][18][19] molybdenum-, [20][21][22][23][24][25][26] ruthenium-, [27] osmium-, [27] and cobalt-catalyzed [28] direct transformations of dinitrogen into ammonia and hydrazine have been achieved by recent intensive experimental works in this field of research.…”
Section: Introductionmentioning
confidence: 99%
“…All rights reserved ] exhibited significantly high catalytic activity. [9,24,25] In order to explain the high catalytic performance, the dimolybdenum Mo(I)Mo(I)-halide species [MoX-N≡N-MoX] (X = halide) is considered to be a key intermediate that enables the direct N≡N bond cleavage. We believe that synergetic experimental and computational investigations on the reactivity of dinitrogen-bridged dimolybdenum complexes will open a new way to the development of more effective catalysts for nitrogen fixation working under ambient reaction conditions.…”
mentioning
confidence: 99%
“…An X-ray diffractionstudy with the use of synchrotron radiation revealed the known structure of C 92 (81/82)CF 3 ) 16 and new structures of IPR C 92 (38)(CF 3 ) 18 and non-classical C 92 (NC)(CF 3 ) 22 . [12] The molecules of new CF 3 derivativeso fC 92 isomersa re shown in Figure1 in two projectionse ach. The molecule of C 92 (38)(CF 3 ) 18 represents the highly trifluoromethylated CF 3 derivativeo fi somer C 92 (38) whereas the compound C 92 (38)(CF 3 ) 14 and severali somerso fC 92 (38)(CF 3 ) 16 have been knownb efore.…”
mentioning
confidence: 99%